A novel and low expensive colorimetric method for quantification of histamine - Ledesma, Silvana Cecilia (2018)
During vinification process, lactic acid bacteria (LABs) are the main microorganisms responsible of biogenic amines (BAs) synthesis, which are organic compounds that affect the human health and quality of the final product. Histamine is the main BA present in wine, and can produce allergic and vascular disorders. The presence of histamine was evaluated by an inexpensive and rapid method implemented in our laboratory, using the principles of technique described by Patange et al. (2005) for the determination of histamine in fish. The procedures were modified and adapted for wine and laboratory broth media. The samples consisted of culture supernatants were obtained in decarboxilating broth medium using a lot of 30 randomly LABs selected from different red wine cellars located in the district of Colalao del Valle of Tucuman and preliminary identified as Pediococcus, Lactobacillus and Oenococcus. Such isolates were previously submitted to a screening in Maijala agar medium and in a commercial decarboxilating Moeller broth medium for the cualitative detection of histidine decarboxylase activity. All the isolated bacteria were adapted previously in MRS-histidine medium by 5 days and then inoculated individually in both media at a viable cell concentration of 106 and incubated by 96 h at 28°C. Only the supernatants obtained from Moeller medium where the bacteria showed positive histidine decarboxilase activity were additionally submitted to the novel colorimetric method development in this study. In addition, an aliquot of commercial red wine sample was used in order to quantify histamine directly in such samples. Appropriate dilutions of a standard Histamine dihydrochloride were performed in distilled water or commercial red wine to obtain a final concentration range between of 0-100 mg/L of the amine in order to achieve a calibration standard curve. The amine was also determined in a commercial red wine supplemented or not with histamine at concentration of 15, 30 and 60 mg/L. The results showed that 17 LABs showed histidine decarboxylase activity in the screening Maijala and Moeller medium. The histamine concentration determined by the colorimetric method showed that the 17 isolates produce different amounts of the amine in Moeller medium, detecting the higher concentration in the supernatants obtained from Lactobacillus pentosus (42.78 mg/L) and Pediococcus damnosus (40.39 mg/L). Histamine was not detected in commercial red wine from a Colalao de Valle wine cellar. In the same commercial wine supplemented with histamine, the detected concentration using the colorimetric assay was close to the expected (16.2, 31.48 and 62.78 mg/L respectively). These results demonstrate that the colorimetric technique may be suitable for routine analysis in monitoring of histamine in wine.